The Role of Physical Education and Sports in Youth Policy (Journal of Pedagogical Inventions and Practices, 2021)
This article deals with the formation of aspirations for a healthy lifestyle among young people, as well as the conditions created for the meaningful organization of youth leisure and the mass development of youth sports. At the same time, educating young people in physical fitness, improving the skills of talented athletes in accordance with modern requirements and international standards, as well as increasing the working capacity and productivity of the working population, intellectuals, and most importantly, prolonging life through a healthy lifestyle. and the importance of physical education